2020
DOI: 10.3389/fphys.2020.603081
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal MiR-769-5p Exacerbates Ultraviolet-Induced Bystander Effect by Targeting TGFBR1

Abstract: Exosomal microRNAs have been investigated in bystander effect, but it is unclear whether microRNA works in ultraviolet radiation–induced bystander effects (UV-RIBEs) and what the underlying mechanism could be. Exosomes from ultraviolet (UV)–irradiated human skin fibroblasts (HSFs) were isolated and transferred to normal HSFs, followed by the detection of proliferation rate, oxidative damage level, and apoptosis rate. Exosomal miRNAs were evaluated and screened with miRNA sequencing and quantitative reverse tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The reduction of ANO1 protein level in exosome group indicated that exosome could inhibit the expression of ANO1, but it is difficult to explain if this reduction is directly or indirectly caused by the exosomes. It is reported that microRNAs (miR), miR-142-3p ( 44 ) and miR-769-5p ( 45 ), carried by exosomes could directly bind with the 3'-UTR of TGF-β1 mRNA, thereby downregulating its mRNA level. In addition, the expression level of ANO1 could also be inhibited by miR-9( 37 ) and miR-381( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of ANO1 protein level in exosome group indicated that exosome could inhibit the expression of ANO1, but it is difficult to explain if this reduction is directly or indirectly caused by the exosomes. It is reported that microRNAs (miR), miR-142-3p ( 44 ) and miR-769-5p ( 45 ), carried by exosomes could directly bind with the 3'-UTR of TGF-β1 mRNA, thereby downregulating its mRNA level. In addition, the expression level of ANO1 could also be inhibited by miR-9( 37 ) and miR-381( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…It could be the bystander effect of radiotherapy, that is, the same effect of radiotherapy on cells, tissues or organs in non-irradiated areas ( Wang et al, 2015 ; Fu et al, 2020 ). After irradiation, cells in the irradiated area can secrete cytokines, small molecular metabolites, exosomes or microvesicles containing various substances, and other media ( Lin et al, 2017 ; Ariyoshi et al, 2019 ; Ni et al, 2020 ; Mukherjee et al, 2021 ), resulting in metabolic disorders, apoptosis, endoplasmic reticulum and golgi dysfunction of cells in non-irradiated areas ( Yakovlev, 2015 ; Jella et al, 2018 ; Mladenov et al, 2018 ; Dong et al, 2020 ; Heeran et al, 2021 ; Yang et al, 2021 ). Earlier studies reported elevated levels of CRP in circulating blood, and splenic cells exhibited enhanced levels of oxidative stress and increased apoptosis after cranial irradiation in rats ( El-Din et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-769-5p is up-regulated in gastric cancer, promotes cancer cell proliferation, and inhibits apoptosis [ 39 ]. Human skin fibroblast exosomes-derived miR-769-5p exacerbates ultraviolet radiation-induced bystander effect through cell-to-cell communication [ 41 ], signifying that miR-769-5p participates in intracellular interactions. It was discovered that miR-769-5p expression was up-regulated in OS cells through bioinformatics analysis and its expression in OS cells and tissues was verified.…”
Section: Discussionmentioning
confidence: 99%